The natural ingredients in Erbil governorate and the possibility of establishing proposed natural reserves and investing them in eco-tourism - Abdulazez, Sozan (Al-Adab Journal, 2023)
The research dealt with multiple definitions of natural reserves, their importance, the reasons for their establishment and their types, as well as the location of the study area, which has a great role in possessing this region a lot of natural ingredients, its geological structure, which is characterized by extreme diversity depending on what the earth layers contain, and it is divided into two terrain regions, the first is the mountainous region Which prevails the northern and northeastern sides with a height of (3600-1000) m, and the second is the semi-mountainous region and is located to the south of the first region with an altitude of (250-1000) m, and the mountains (Heybet Sultan, Bawaji and Bayramam) represent the natural borders between the two regions.The mountainous region in the study area is characterized by the ideal temperatures to attract the population (18-25) degrees Celsius and the degree of comfort in the months (May, June, July, August, September and October) at Mercosur station, Choman and Rwanduz and at Soran station in the months (April, May and (September and October), as for the semi-mountainous region in Erbil and Koya station, we find ideal temperatures in the spring and autumn months, especially the months (April, May, October and November), there are water resources of all kinds, surface and groundwater, in all directions of the study area The proposed reserves have a distinct inter-regional system in the region (endemic animal and plant groups) whether in value or scarcity in addition to the biological diversity of the life patterns in them. (12) sites have been identified as natural reserves that differ from each other in area and astronomical location. ) natural reserves, and in the semi-mountainous region (3) reserves only. And natural reserves are considered the basic structure in a sound environmental management, especially reserves close to tourist areas, to benefit from tourism income for the benefit of the local population and to preserve environmental resources. The basic environmental elements (climate, landscapes, water bodies and natural formations) that are distinguished to create an environment that is conducive to tourism development, and to find a mechanism to follow up and implement them, and to intensify education and awareness programs at all levels and the participation of government agencies and NGOs with direct government intervention.